Survey of Inmates of Federal Correctional Facilities, 1991 ([Verlag nicht ermittelbar], 1994)
This survey provides nationally representative data on persons held in federal prisons. The survey was designed to supply information on individual characteristics of prison inmates, such as their current offenses and sentences, criminal histories, prior drug and alcohol use and treatment, gun possession and use, gang membership, and family background. Data on characteristics of victims and on prison activities, programs, and services are provided as well.